Decolonising the Human Reflections from Africa on difference and oppression - Steyn, Melissa (Wits University Press, 2021)
"Decolonising the Human examines the ongoing project of constituting 'the human' in light of the durability of coloniality and the persistence of multiple oppressions. The 'human' emerges as a deeply political category, historically constructed as a scarce existential resource. Once weaponised, it allows for the social, political and economic elevation of those who are centred within its magic circle, and the degradation, marginalisation and immiseration of those excluded as the different and inferior Other, the less than human. Speaking from Africa, a key site where the category of the human has been used throughout European modernity to control, exclude and deny equality of being, the contributors use decoloniality as a potent theoretical and philosophical tool, gesturing towards a liberated, pluriversal world where human difference will be recognised as a gift, not used to police the boundaries of the human. Here is a transdisciplinary critical exploration of a wide range of subjects, including history, politics, philosophy, sociology, anthropology and decolonial studies. "